2005
DOI: 10.1002/bip.20420
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanism of desmopressin binding in vasopressin V2 receptor versus vasopressin V1a and oxytocin receptors: Molecular dynamics simulation of the agonist‐bound state in the membrane–aqueous system

Abstract: The vasopressin V2 receptor (V2R) belongs to the Class A G protein-coupled receptors (GPCRs). V2R is expressed in the renal collecting duct (CD), where it mediates the antidiuretic action of the neurohypophyseal hormone arginine vasopressin (CYFQNCPRG-NH2, AVP). Desmopressin ([1-deamino, 8-D]AVP, dDAVP) is strong selective V2R agonist with negligible pressor and uterotonic activity. In this paper, the interactions responsible for binding of dDAVP to vasopressin V2 receptor versus vasopressin V1a and oxytocin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 111 publications
(140 reference statements)
2
17
0
Order By: Relevance
“…At the beginning of building the model we have used the initial model of activated V2R, so we were able to observe its characteristic conformational changes during MD simulation. Accordingly, we have verified previously proposed V2R amino acid residues responsible for vasopressin and Gsa (Ile 382 -Leu 394 ) binding [122,120,121] and we have found that they are mutually consistent. The analyzed deviations of 7TM observed during unconstrained MD simulation and presented as the RMSd evolution accompanying the MD progress are also consistent with previous assumptions.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…At the beginning of building the model we have used the initial model of activated V2R, so we were able to observe its characteristic conformational changes during MD simulation. Accordingly, we have verified previously proposed V2R amino acid residues responsible for vasopressin and Gsa (Ile 382 -Leu 394 ) binding [122,120,121] and we have found that they are mutually consistent. The analyzed deviations of 7TM observed during unconstrained MD simulation and presented as the RMSd evolution accompanying the MD progress are also consistent with previous assumptions.…”
Section: Discussionsupporting
confidence: 86%
“…We have only used them as a biased criterion of accuracy of changes during MD simulation. The retention of previously reported interactions [120,121] has let us confirm as to current MD condition being correct. All currently identified interactions agree with those found previously, and reported by Ś lusarz et al [121] (see Table 3).…”
Section: Analysis Of Interactions Stabilizing the Dimer/ Tetramer Intsupporting
confidence: 54%
See 1 more Smart Citation
“…compbio.ucsf.edu/, entry name o43192 _ HUMAN; University of California San Francisco, San Francisco, CA, USA). Moreover, the TM structure of our model appeared to be similar to Susarz's model [26], considering the positional relationship of each residue.…”
Section: Discussionmentioning
confidence: 77%
“…The equivalent arginyl (R46 and R34 in V 1a R and OTR, respectively) has been identified as playing a critical role in high affinity agonist binding [45,46]. Moreover, the molecular basis for the significance of this residue for dDAVP binding in V 2 R has been proposed in our earlier paper [38]. Other crucial residue which appears in V 2 R is the nonconserved D103 located in the first extracellular loop.…”
Section: Interaction With Vasopressin/oxytocin Receptorsmentioning
confidence: 95%